POTENSI RHIZOBAKTERI DARI TANAMAN KUBIS (Brassica oleracea var. capitata L.) DAERAH GETASAN SEMARANG SEBAGAI AGEN BIOBAKTERISIDA TERHADAP PATOGEN Xanthomonas campestris - Maya Fitriana Ilul Fahmi; Anto Budiharjo; Agung Suprihadi (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2014)
Rhizobacteria are bacteria that live around plant roots but do not cause negative effects on their host and are known to act as a biobactericide agent. The use of chemical-based pesticide against plant pathogen can be replaced with rhizobacteria. The objectives of this research were to isolate rhizobacteria from cabbage, explored from Getasan, Semarang and to determine the ability of the isolates to inhibit pathogens Xanthomonas campestris causing black rot on cabbage in vitro. The research concisted of rhizobacterial isolation, morphologic bacterial characterization, antibacterial test, and molecular and biochemical identification of the isolates. The isolation obtained seventeen rhizobacterial isolates. Four isolates (K.1, K.3, K.9 and K.12) showed potency as an biobactericide agent against pathogenic X. campestris. K.9 had the best ability to inhibit the growth of X.campestris by 12,6 mm. Based on molecular identification K.9 was Bacillus cereus strains BF15. Morphology and Biochemistry test showed that isolates K.9 is gram positive bacteria shaped bacilli, able to form an endospore, positive in hydrolysing starch , fermentation glucose, motile, aerobic and negative in the fermentation of manitol and arabinosa. Keywords : Antibacterial, Rhizobacteria, Cabbages, black rot disease, Xanthomonas. campestris